A Qualitative Study on Performance, Investment Decisions, and Strategic Approaches - Sahrul Ponto; Muhamad Aqsa; Fajar Rina Sejati; Kartim Kartim (Amkop Management Accounting Review (AMAR), 2024)
This qualitative study delves into financial management strategies within organizational contexts, focusing on performance optimization, investment decisions, and strategic approaches. The research aims to understand these strategies and their implications comprehensively. Data from peer-reviewed articles, books, and reports were synthesized using thematic analysis. Findings reveal multifaceted performance optimization strategies, including operational efficiency enhancement, cost control, and performance measurement. Investment decision-making involves thorough evaluation, risk assessment, and strategic alignment influenced by behavioral biases. Strategic approaches emphasize long-term planning, adaptive strategies, and financial risk management. The study contributes to theoretical frameworks such as agency theory and behavioral finance. For practitioners, it underscores the importance of aligning financial goals with organizational objectives, leveraging technology, and addressing biases. Key findings advocate for holistic financial management strategies to enhance performance and adapt to dynamic environments.